2016
DOI: 10.1016/j.bbi.2016.07.158
|View full text |Cite
|
Sign up to set email alerts
|

NOX2 drives M1-like microglial/macrophage activation and neurodegeneration following experimental traumatic brain injury

Abstract: Following traumatic brain injury (TBI), activation of microglia and peripherally derived inflammatory macrophages occurs in association with tissue damage. This neuroinflammatory response may have beneficial or detrimental effects on neuronal survival, depending on the functional polarization of these cells along a continuum from M1-like to M2-like activation states. The mechanisms that regulate M1-like and M2-like activation after TBI are not well understood, but appear in part to reflect the redox state of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
140
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 160 publications
(155 citation statements)
references
References 70 publications
14
140
0
Order By: Relevance
“…Given that NOX2 −/− TBI mice exhibit enhanced anti-inflammatory activation that is associated with improved outcomes following TBI [24], we set out to investigate mechanisms of NOX2-dependent macrophage phenotype switching using the LPS/IL-4 stimulation model. WT and NOX2 −/− BMDMs were treated with LPS/IL-4 for 24 h, and pro and anti-inflammatory activation markers were assessed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that NOX2 −/− TBI mice exhibit enhanced anti-inflammatory activation that is associated with improved outcomes following TBI [24], we set out to investigate mechanisms of NOX2-dependent macrophage phenotype switching using the LPS/IL-4 stimulation model. WT and NOX2 −/− BMDMs were treated with LPS/IL-4 for 24 h, and pro and anti-inflammatory activation markers were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…NOX2 is highly expressed in macrophage/microglia up to 12 months after moderate-to-severe TBI [21], and inhibition of NOX2 is neuroprotective and reduces inflammatory-mediated neuronal cell death after TBI [2326]. We recently reported that NOX2 inhibition also enhances anti-inflammatory activation of macrophage/microglia following TBI [24]. Thus, NOX2 may act as a critical switch between pro- and anti-inflammatory phenotypes after TBI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The functions of microglia become more significant in response to a CNS insult such as ischemia. Increasing evidence suggests that an increase in the brain M2/M1 ratio and increases of M2 microglial proteins have anti-inflammatory properties and provide a neuroprotective effect [36,37]. IL-4 and IL-10 are markers secreted by M2 microglial cells, while TNF-α, IL-6 and iNOS are markers secreted by M1 microglial cells [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%